2012
DOI: 10.1007/s00223-012-9684-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Glucocorticoids on Serum Markers of Osteoclasts, Osteoblasts, and Osteocytes

Abstract: The aim of this study was to investigate the acute effects of oral glucocorticoids in doses used in clinical practice on biochemical indices of the function of osteoclasts, osteoblasts, and osteocytes. In 17 adult patients suffering from various medical pathologies requiring systemic steroid therapy that were never before treated with glucocorticoids, glucocorticoid treatment was initiated (mean prednisolone equivalent dose of 23.1 ± 12.7 mg/day, range 10-50). Fasting morning serum concentrations of osteocalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 50 publications
6
46
0
1
Order By: Relevance
“…These data indicate that osteoclast absorption was greater than osteoblast formation. Recently, it was reported that overexpression of DKK-1 during inflammation not only resulted in inhibition of bone formation but also stimulated the activity of osteoclasts [34][35][36]. In our study, excess DKK-1 was found in the ankle and femur of CIA rats at 8 weeks after immunization.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These data indicate that osteoclast absorption was greater than osteoblast formation. Recently, it was reported that overexpression of DKK-1 during inflammation not only resulted in inhibition of bone formation but also stimulated the activity of osteoclasts [34][35][36]. In our study, excess DKK-1 was found in the ankle and femur of CIA rats at 8 weeks after immunization.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, in the process of osteoporosis caused by CIA, upregulation of DKK-1 not only reduced systemic bone mass, as a result of activation of osteoclasts, resulting in enhanced bone resorption [35,36], but also affected bone growth by inhibiting the differentiation of osteoblasts [30] as well as the transport of substances osteoblasts need. Furthermore, our findings suggest that activation of the Wnt signaling pathway by inhibition of DKK-1 is a target for prevention and treatment of osteoporosis induced by RA.…”
Section: Discussionmentioning
confidence: 86%
“…Thirdly , it is likely that the marked change in the drug treatment and in particular the use of glucocorticoids could contribute to the rapid decrease of sclerostin after transplantation. In a study with 17 patients suffering from various medical pathologies requiring systemic steroid therapy, acute treatment with glucocorticoids was found to decrease sclerostin levels, an effect that is probably linked to glucocorticoid-induced apoptosis of osteocytes [19]. Contrary, Gifre et al showed an increase in sclerostin values in patients treated one year with glucocorticoids [20].…”
Section: Discussionmentioning
confidence: 99%
“…after short-and long-time treatment with glucocorticoids in mice and rats [Yao et al, 2008;Ren et al, 2015a], but also in male humans after 96-hour treatment with dexamethasone [Brabnikova Maresova et al, 2013]. They discussed apoptotic effects of dexamethasone on osteocytes as a possible reason.…”
Section: Discussionmentioning
confidence: 99%